Why is there no “third” Korean nuclear crisis? - Yoon, Seongwon (Frontiers in Political Science, 2025)
IntroductionThe knowledge and technology North Korea possessed concerning nuclear weapons systems during the first nuclear crisis in the period from 1993 to 1994 are incomparable to what they hold today. While the discourse on North Korea’s nuclear threat in the 2020s remains largely the same as it was in the early 1990s, the significant advancements in the country’s nuclear technology are noteworthy.MethodsUsing the concept of crisis and securitization, this article examines the patterns of discourse during the first and second Korean nuclear crises and explores the factors contributing to the relative absence of discourse on a third nuclear crisis.ResultsThis analysis reveals that the securitization process regarding North Korea’s nuclear threat has become routinized, thereby diminishing its performative urgency.DiscussionFirst, this analysis enables a reflexive examination of the nuclear crisis, challenging the casual use of the term crisis. Second, it facilitates an analysis that minimizes ideological bias. Third, it sheds light on the underlying permissive factors sustaining the protracted discourse on North Korea’s nuclear threat. Rather than proposing an illusory solution, this article constructs a novel framework for analyzing the Korean nuclear crisis and suggests a more informed direction for future securitization efforts.